Air Warfare over Ukraine and International Humanitarian Law - Sotula, Oleksandr; Piątkowski, Mateusz (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The Russian aggression against Ukraine involves extensive use of air power, proving that without the sufficient level of air control, the combat operations on the ground face significant operational challenges. The use of air power raises questions regarding the legality of the aerial actions conducted over Ukraine. This conflict in the air domain is characterised by separate campaigns. The first one was a battle over the air superiority of Ukraine, which was relatively short in time (February–April 2022), albeit intense, and lost by the Russian Air Force due to the inability to destroy Ukrainian air defence assets and Ukrainian military aviation. The second one, still in progress at the moment this article is being written, looks to become an unresolved contest of attrition, as both belligerents vastly increased their air disruption capabilities. In particular, during the last period of the first phase, it is believed that many of the Russian air strikes were, in fact, indiscriminate or deliberately directed against civilian objectives. The aim of the article is to analyse the overall conduct of the air war over Ukraine and pinpoint the legal challenges in assessing the legality of such air operations. In the context of available information, the paper will seek to understand the legal framework concerning the destruction of the An-225 at the Hostomel airport during the first phase of hostilities, the use of certain aerial weapons, and the selection of targets.